The use of problem-based learning (PBL) in higher education - Coronel Tello, Ana Eylin (2023)
This article is a descriptive bibliographic review related to the use of Problem Based Learning (PBL) in Higher Education in the last five years, from 2017 to 2021. The main objective of this review is focused on a bibliometric analysis to state PBL definitions, advantages and application in different study fields. Based on the aforementioned, it is possible to contrast and report if this new strategy is likely to be implemented in universities. The methodology used was a systematic and analytic review of different information found in databases, repositories and indexed journals among others such as Alicia, Dialnet, Google Scholar, Scielo, Scopus and Web of Science. The search criteria were originality, open access and international outreach.